Polyimide varnish

KR103013719B1Active Publication Date: 2026-09-02NISSAN CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020227026003
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-13
Filing Date
2021-03-04
Publication Date
2026-09-02
Estimated Expiration
2041-03-04

Smart Images

  • Figure 112022078166691-PCT00050_ABST
    Figure 112022078166691-PCT00050_ABST
Patent Text Reader

Abstract

The present invention provides a polyimide varnish capable of obtaining a polyimide film with high membrane permeability even when using a polyimide having a diphenylamine backbone. The polyimide varnish comprises at least one block copolymer selected from the group consisting of a polyimide precursor having a block (b1) having a repeating unit represented by the following formula (1) and a block (b2) having a repeating unit represented by the following formula (2), and a polyimide obtained by imidizing the polyimide precursor. (X1 represents a tetravalent organic group. X2 represents a tetravalent organic group derived from an acyclic aliphatic tetracarboxylic acid dihydride or a tetravalent organic group represented by the following formula (X2). Y1 represents a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. Y2 represents a divalent organic group having a diphenylamine backbone. Two R1s and R2s each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and two Z1s and Z2s each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms that may have substituents, an alkenyl group having 2 to 10 carbon atoms that may have substituents, an alkynyl group having 2 to 10 carbon atoms that may have substituents, a tert-butoxycarbonyl group, or a 9-fluorenylmethoxycarbonyl group.) (R21–R24 each independently represent a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a phenyl group.)
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyimide varnish having a diphenylamine backbone and capable of obtaining a polyimide film having high membrane permeability. Background Technology

[0002] Polyimide is widely used as a protective material in the electrical and electronic fields due to its characteristics of high mechanical strength, heat resistance, and solvent resistance. Specifically, when used as a liquid crystal alignment layer for liquid crystal displays, it is common practice to form a polyimide film of 0.05 to 0.2 μm on a transparent support substrate to which a transparent electrode is attached, and to form a thin polyimide film on various support substrates.

[0003] To form a polyimide film, it is common practice to apply a polyimide varnish, in which a polyimide (precursor) is dissolved in a suitable organic solvent, onto a supporting substrate by methods such as spin coating, offset printing, gravure printing, flexographic printing, or inkjet printing, and then perform a heat treatment.

[0004] Recently, polyimides having a diphenylamine backbone have been proposed in Patent Document 1 or Patent Document 2 in order to impart various properties to liquid crystal alignment films. Prior art literature

[0005] WO2004 / 021076 Public Notice WO2013 / 008822 The problem to be solved

[0006] It has been revealed that polyimides having a diphenylamine backbone tend to have a reduced permeability of the resulting membrane and are susceptible to the influence of the raw monomer used in the polymerization reaction. As a result of investigations by the inventors, polyimides obtained using specific alicyclic tetracarboxylic acid dihydrides showed a significantly reduced permeability of the resulting membrane. After investigating various causes, it was found that the membrane permeability decreases when the polyimide (precursor) adopts a specific molecular arrangement. Furthermore, it was revealed that the structure of the imide precursor during heat treatment is one of the factors causing discoloration.

[0007] The objective of the present invention is to provide a polyimide varnish that, taking into account the above circumstances, can obtain a polyimide film with high film permeability even when using a polyimide having a diphenylamine backbone. means of solving the problem

[0008] As a result of conducting diligent research to achieve the above objective, the inventors discovered that a polyimide varnish containing a specific block copolymer is effective for achieving the above objective, and thus completed the present invention.

[0009] The present invention is based on these findings and is centered on the following.

[0010] A polyimide varnish containing at least one block copolymer selected from the group consisting of a polyimide precursor having a block (b1) having a repeating unit represented by the following formula (1) and a block (b2) having a repeating unit represented by the following formula (2), and a polyimide obtained by imidizing the polyimide precursor.

[0011] [Chemical Formula 1]

[0012]

[0013] (X1 represents a tetravalent organic group. X2 represents a tetravalent organic group derived from an acyclic aliphatic tetracarboxylic acid dihydride or a tetravalent organic group represented by the following formula (X2). Y1 represents a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. Y2 represents a divalent organic group having a diphenylamine backbone. Two R1s and R2s each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and two Z1s and Z2s each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms that may have substituents, an alkenyl group having 2 to 10 carbon atoms that may have substituents, an alkynyl group having 2 to 10 carbon atoms that may have substituents, a tert-butoxycarbonyl group, or a 9-fluorenylmethoxycarbonyl group.)

[0014] [Chemical Formula 2]

[0015]

[0016] (R 21 ~ R 24 Each represents, independently, a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a phenyl group.

[0017] In addition, in this specification, * indicates a bond loss in any case. Boc indicates a tert-butoxycarbonyl group. Also, in this specification, halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. Effects of the invention

[0018] According to the polyimide varnish of the present invention, a polyimide film with high film transmittance can be obtained even when using a polyimide having a diphenylamine backbone. Furthermore, the polyimide varnish of the present invention enables a polyimide film with high film transmittance, while simultaneously enabling good polyimide film characteristics in other aspects (e.g., voltage retention rate, residual DC voltage, afterimage characteristics, rubbing resistance). In addition, the present invention provides a method for manufacturing the polyimide varnish.

[0019] Although the mechanism by which the above effect of the present invention is obtained is not necessarily clear, it is believed that the following is one of the factors.

[0020] That is, since the reaction between a diamine component having a diphenylamine backbone and an acyclic aliphatic tetracarboxylic acid dihydride or a specific alicyclic tetracarboxylic acid dihydride proceeds at a relatively low temperature, discoloration caused by oxidation of the diamine component in the reaction system can be suppressed compared to a reaction at a high temperature. In addition, a membrane using a polyimide precursor obtained using a diamine having a diphenylamine backbone and an acyclic aliphatic tetracarboxylic acid dihydride or a specific alicyclic tetracarboxylic acid dihydride can lower the amine donority and obtain a polyimide membrane with high membrane permeability because it is easy to thermally imidize during heat treatment. Brief explanation of the drawing

[0021] FIG. 1 is a diagram showing the transmittance obtained using the liquid crystal alignment agent (A-1) of Example 1 and the liquid crystal alignment agent (B-1) of Comparative Example 1. Specific details for implementing the invention

[0022] <Block Copolymer>

[0023] The polyimide varnish of the present invention contains at least one block copolymer selected from the group consisting of a polyimide precursor having a block (b1) having a repeating unit represented by the following formula (1) and a block (b2) having a repeating unit represented by the following formula (2), and a polyimide obtained by imidizing the polyimide precursor. That is, the polyimide varnish of the present invention contains at least one block copolymer selected from the group consisting of a polyimide precursor having the block (b1) and block (b2) and also not having an imide ring structure, and a polyimide obtained by imidizing the polyimide precursor, wherein the polyimide has any of the repeating units of the imidized repeating unit of the formula (1), the imidized repeating unit of the formula (2), or other imidized repeating units.

[0024] [Chemical Formula 3]

[0025]

[0026] (X1 represents a tetravalent organic group. X2 represents a tetravalent organic group derived from an acyclic aliphatic tetracarboxylic acid dihydride or a tetravalent organic group represented by the following formula (X2). Y1 represents a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. Y2 represents a divalent organic group having a diphenylamine backbone. Two R1s and R2s each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and two Z1s and Z2s each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms that may have substituents, an alkenyl group having 2 to 10 carbon atoms that may have substituents, an alkynyl group having 2 to 10 carbon atoms that may have substituents, a tert-butoxycarbonyl group, or a 9-fluorenylmethoxycarbonyl group.)

[0027] [Chemical Formula 4]

[0028]

[0029] (R 21 ~ R 24 Each represents, independently, a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a benzene ring.

[0030] In formula (1), X1 preferably represents a tetravalent organic group derived from a tetracarboxylic acid dihydride, and more preferably represents at least one type selected from the group consisting of structures represented by the following formulas (X1-1) to (X1-12).

[0031] [Chemical Formula 5]

[0032]

[0033] In formula (1), Y1 preferably represents a divalent organic group having 3 to 50 carbon atoms having a structure represented by the following formulas (S1) to (S3), or a divalent organic group having 3 to 50 carbon atoms not having a structure represented by the above formulas (S1) to (S3). Furthermore, the divalent organic group having 3 to 50 carbon atoms having a structure represented by the above formulas (S1) to (S3) and the divalent organic group having 3 to 50 carbon atoms not having a structure represented by the above formulas (S1) to (S3) do not have a diphenylamine backbone as described above. A specific example of a divalent organic group having 3 to 50 carbon atoms that does not have a structure represented by the above formulas (S1) to (S3) is a divalent organic group having a nitrogen-containing heterocyclic ring within the molecule, such as the following formulas (2a-1) to (2a-14); a divalent organic group having a radical initiating function, such as the following formulas (2b-1) to (2b-5); a divalent organic group having a carboxyl group, such as the following formulas (2c-1) to (2c-2); a group having "-N(D)-" (D represents a tert-butoxycarbonyl group), such as the following formulas (2d-1) to (2d-7); a group having photo-oriented properties, such as the following formulas (2e-1) to (2e-11); a divalent organic group having an oxygen-containing heterocyclic ring, such as (2f-1) to (2f-3); or the following formula (2-1) to Examples include divalent organic groups derived from aromatic diamines that do not have a side chain with three or more carbon atoms, such as (2-35).

[0034] [Chemical Formula 6]

[0035]

[0036] (X 1 and X 2 is, each independently, single bond, -(CH2) a - (a is an integer from 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -COO-, -OCO- or -((CH2) a1-A1) m1 - represents. Among these, a1 is independently an integer from 1 to 15, A1 is independently an oxygen atom or -COO-, and m1 is from 1 to 2. G 1 and G 2 represents, respectively, a divalent cyclic group selected from a divalent aromatic group having 6 to 12 carbon atoms and a divalent alicyclic group having 3 to 8 carbon atoms. Any hydrogen atom on the cyclic group may be substituted. m and n are each independently integers from 0 to 3, and m + n is 1 to 4. R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms, and R 1 Any hydrogen atom forming may be substituted with a fluorine atom. If m, n, and m1 are 2 or more, there are multiple Xs. 1 , X 2 , G 1 , G 2 , a1, m1, and A1 each independently have the above definition. Substituents that may be substituted for any hydrogen atom on the cyclic group include, for example, substituents selected from the group consisting of a halogen atom, a halogen atom-containing alkyl group, a halogen atom-containing alkoxy group, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, and a heteroatom-containing group in which any carbon-carbon bond of the halogen atom-containing alkyl group, the halogen atom-containing alkoxy group, the alkyl group, the alkoxy group, and the alkenyl group is interrupted by an oxygen atom.

[0037] [Chemical Formula 7]

[0038]

[0039] (X 3It represents a single bond, -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CH2O-, -COO-, or -OCO-. R 2 represents an alkyl group having 1 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms, and R 2 Any hydrogen atom forming it may be replaced with a fluorine atom.)

[0040] [Chemical Formula 8]

[0041]

[0042] (X 4 represents -CONH-, -NHCO-, -O-, -CH2O-, -COO-, or -OCO-. R 3 It represents a structure having a steroid backbone.

[0043] [Chemical Formula 9]

[0044]

[0045] [Chemical Formula 10]

[0046]

[0047] [Chemical Formula 11]

[0048]

[0049] [Chemical Formula 12]

[0050]

[0051] [Chemical Formula 13]

[0052]

[0053] [Chemical Formula 14]

[0054]

[0055] [Chemical Formula 15]

[0056]

[0057] [Chemical Formula 16]

[0058]

[0059] In formula (1), at least one of Y1 is preferably a divalent organic group having a structure represented by formulas (S1) to (S3), a divalent organic group having a nitrogen-containing heterocyclic ring within the molecule, or a divalent organic group represented by formulas (2-1) to (2-35), in order to increase the transmittance of the polyimide film obtained. Specific examples of divalent organic groups having a structure represented by formulas (S1) to (S3) include groups obtained by removing two amino groups from a diamine represented by formulas (Ys-1) to (Ys-13).

[0060] [Chemical Formula 17]

[0061]

[0062] [Chemical Formula 18]

[0063]

[0064] (However, among the foods, X v1 ~ X v4 , X p1 ~ X p8 은, each independently, -(CH2) a - (a is an integer from 1 to 15), representing -CONH-, -NHCO-, -CO-N(CH3)-, -NH-, -O-, -CH2O-, -CH2-OCO-, -COO-, or -OCO-, and X v5 represents -O-, -CH2O-, -CH2-OCO-, -COO-, or -OCO-, and X V6 ~ X V7 , X s1 ~ X s4 Each represents -O-, -CH2O-, -COO-, or -OCO- independently. X a ~ X f is a single bond, -O-, -NH-, or -O-(CH2) m Represents -O-, and R v1 ~ R v4 , R 1a ~ R1h are independently, -C n H 2n+1 (n is an integer from 1 to 20), or -OC n H 2n+1 (n represents an integer from 2 to 20. m represents an integer from 1 to 8.)

[0065] In formula (1), the two R1s preferably each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. The two Z1s preferably each independently represent a hydrogen atom or a methyl group.

[0066] In equation (1), X1, Y1, R1, and Z1 may each be of one type or two or more types.

[0067] A block (b1) having a repeating unit represented by Equation (1) may have any repeating unit other than the repeating unit represented by Equation (1).

[0068] The content of the repeating unit represented by formula (1) is preferably 5 to 90 mol% with respect to the sum of the repeating units of block (b1) and block (b2), more preferably 10 to 80 mol%, and particularly preferably 20 to 70 mol%.

[0069] In formula (2), the “acyclic aliphatic tetracarboxylic acid dihydride” of X2 is an acid dihydride obtained by intramolecular dehydration of four carboxyl groups bonded to a chain-type hydrocarbon structure. However, it is not necessary to be composed solely of a chain-type hydrocarbon structure, and it may have an alicyclic structure or an aromatic ring structure in part thereof.

[0070] Specific examples of "acyclic aliphatic tetracarboxylic acid dihydride" include the following compounds (T 2a ...can be cited.

[0071] [Chemical Formula 19]

[0072]

[0073] (X 2a is, the following formula (X 2a -1) ∼ (X 2a -5) Represents at least one type selected from the group consisting of structures represented by.

[0074] [Chemical Formula 20]

[0075]

[0076] In formula (2), X2 preferably represents at least one type selected from the group consisting of structures represented by the following formulas (X2-1) to (X2-4).

[0077] [Chemical Formula 21]

[0078]

[0079] In Equation (2), Y2 preferably represents a structure represented by the following Equation (d2).

[0080] [Chemical Formula 22]

[0081]

[0082] (A1 represents a single bond, -NR- (R represents a hydrogen atom or a monovalent organic group), -O-, -C(=O)-, -C(=O)NR- (R represents a hydrogen atom or a monovalent organic group), -C(=O)O-, or a divalent organic group. R1 and R2 each independently represent a hydrogen atom or a monovalent organic group. If n is 2, multiple A1 and R2 exist, each independently having the above definition.)

[0083] Examples of divalent organic groups in A1 include -CH2-, -C(CH3)2-, an alkylene group having 2 to 20 carbon atoms, or a divalent organic group in which a part of the methylene group of the alkylene group is substituted with -NR- (where R represents a hydrogen atom or a monovalent organic group), -O-, -C(=O)-, -C(=O)NR- (where R represents a hydrogen atom or a monovalent organic group), or -C(=O)O-.

[0084] Examples of the monovalent organic group in formula (d2) include an alkyl group having 1 to 10 carbon atoms, such as a methyl group or an ethyl group; an alkyl group having 1 to 10 carbon atoms, such as a trifluoroalkyl group; an alkoxyalkyl group having 1 to 10 carbon atoms; a group containing a thermally detachable group; or a group in which a portion of the methylene group having the alkyl group is substituted with -O-, -C(=O)-, or -C(=O)NR- (where R represents a hydrogen atom or a methyl group) (except for the group containing the thermally detachable group). Examples of groups including thermally desoluble groups include carbamate-based protecting groups such as tert-butoxycarbonyl groups (Boc groups), benzyloxycarbonyl groups, 9-fluorenylmethyloxycarbonyl groups, or allyloxycarbonyl groups, or groups in which a portion of the hydrogen atoms of the alkyl groups are substituted with the group "*-OE" (where E represents a hydrogen atom or a carbamate-based protecting group).

[0085] Y2 is a more desirable structure, and the following equations (d2-1) to (d2-13) can be cited.

[0086] [Chemical Formula 23]

[0087]

[0088] [Chemical Formula 24]

[0089]

[0090] In formula (2), the two R2s preferably each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. The two Z2s preferably each independently represent a hydrogen atom or a methyl group.

[0091] In equation (2), X2, Y2, R2, and Z2 may each be of one type or two or more types.

[0092] A block (b2) having a repeating unit represented by Equation (2) may have any repeating unit other than the repeating unit represented by Equation (2).

[0093] The content of the repeating unit represented by formula (2) is preferably 5 to 90 mol% with respect to the sum of the repeating units of block (b1) and block (b2), more preferably 10 to 80 mol%, and particularly preferably 20 to 70 mol%.

[0094] The ratio of the total number of moles of repeating units represented by Formula (1) to the total number of moles of repeating units represented by Formula (2) per molecule of the block copolymer of the present invention is preferably 9:1 to 1:9, more preferably 8:2 to 2:8, and particularly preferably 7:3 to 3:7.

[0095] If the ratio of the total moles of repeating units is within this range, it is excellent in that a high permeability of the membrane is obtained.

[0096] The block copolymer of the present invention may have any repeating unit other than the block (b1) having a repeating unit represented by Formula (1) and the block (b2) having a repeating unit represented by Formula (2).

[0097] <Preparation of Polyimide Precursor (Polyamic Acid)>

[0098] Examples of polyimide precursors used in the present invention include polyamic acid, polyamic acid ester, etc.

[0099] The polyamic acid, which is a polyimide precursor used in the present invention, can be prepared, for example, by a manufacturing method having the following processes (I) to (II). A process (I) of obtaining a block (b1) by reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (1-T) with a diamine component comprising a diamine represented by the following formula (1-D), and

[0100] A process (II) for obtaining a polyimide precursor comprising block (b1) and block (b2) by adding and reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (2-T) and a diamine component comprising a diamine represented by the following formula (2-D) to block (b1).

[0101] [Chemical Formula 25]

[0102]

[0103] (X1, X2, Y1, and Y2 are the same as those defined in Equations (1) and (2).)

[0104] In addition, among the derivatives of the tetracarboxylic acid dihydride mentioned above, tetracarboxylic acid, tetracarboxylic acid dihalide, tetracarboxylic acid diester dichloride, tetracarboxylic acid diester, etc.

[0105] The reaction temperature in the above process (II) is preferably a lower temperature than the reaction temperature in the above process (I), more preferably a lower temperature than the reaction temperature in the above process (I) by at least 10°C, and particularly preferably a lower temperature than the reaction temperature in the above process (I) by at least 20°C. A polyimide varnish containing a block copolymer obtained by reacting within the above range can be obtained with a polyimide film having high permeability because oxidation during the reaction can be suppressed in that the heating does not require a high temperature.

[0106] Preferably, the reaction temperature in process (I) is 0 to 150 ℃, and the reaction temperature in process (II) is -20 to 130 ℃. More preferably, the reaction temperature in process (I) is 5 to 100 ℃, and the reaction temperature in process (II) is -5 to 80 ℃.

[0107] The tetracarboxylic acid component in process (I) may include any tetracarboxylic acid dihydride or derivative thereof other than the tetracarboxylic acid dihydride or derivative thereof represented by the above formula (1-T), but preferably consists of the tetracarboxylic acid dihydride or derivative thereof represented by the above formula (1-T).

[0108] The diamine component in process (I) may include any diamine other than the diamine represented by formula (1-D), but preferably consists of the diamine represented by formula (1-D).

[0109] The tetracarboxylic acid component in process (II) may include any tetracarboxylic acid dihydride or derivative thereof other than the tetracarboxylic acid dihydride or derivative thereof represented by the formula (2-T), but preferably consists of the tetracarboxylic acid dihydride or derivative thereof represented by the formula (2-T).

[0110] The diamine component in process (II) may include any diamine other than the diamine represented by formula (2-D), but preferably consists of the diamine represented by formula (2-D).

[0111] The polyamic acid, which is a polyimide precursor used in the present invention, can also be produced by a manufacturing method having, for example, the following processes (III) to (V).

[0112] A process (III) for obtaining block (b1) by reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (1-T) with a diamine component comprising a diamine represented by the following formula (1-D), and

[0113] A process (IV) for obtaining block (b2) by reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (2-T) with a diamine component comprising a diamine represented by the following formula (2-D), and

[0114] A process (V) for obtaining a polyimide precursor comprising block (b1) obtained in process (III) and block (b2) obtained in process (IV) by coupling them.

[0115] [Chemical Formula 26]

[0116]

[0117] (X1, X2, Y1, and Y2 are the same as those defined in Equations (1) and (2).)

[0118] The reaction temperature in the above process (IV) is preferably lower than the reaction temperature in the above process (III), more preferably at least 10°C lower than the reaction temperature in the above process (III), and particularly preferably at least 20°C lower than the reaction temperature in the above process (III). A polyimide varnish containing a block copolymer obtained by reacting within the above range can be obtained with a polyimide film having high permeability because oxidation during the reaction can be suppressed in that the heating does not require a high temperature.

[0119] Preferably, the reaction temperature in process (III) is 0 to 150 ℃, and the reaction temperature in process (IV) is -20 to 130 ℃. More preferably, the reaction temperature in process (III) is 5 to 100 ℃, and the reaction temperature in process (IV) is -5 to 80 ℃.

[0120] The tetracarboxylic acid component in process (III) may include any tetracarboxylic acid dihydride or derivative thereof other than the tetracarboxylic acid dihydride or derivative thereof represented by formula (1-T), but preferably consists of the tetracarboxylic acid dihydride or derivative thereof represented by formula (1-T).

[0121] The diamine component in process (III) may include any diamine other than the diamine represented by formula (1-D), but preferably consists of the diamine represented by formula (1-D).

[0122] The tetracarboxylic acid component in process (IV) may include any tetracarboxylic acid dihydride or derivative thereof other than the tetracarboxylic acid dihydride or derivative thereof represented by the formula (2-T), but preferably consists of the tetracarboxylic acid dihydride or derivative thereof represented by the formula (2-T).

[0123] The diamine component in process (IV) may include any diamine other than the diamine represented by formula (2-D), but preferably consists of the diamine represented by formula (2-D).

[0124] The method of coupling block (b1) and block (b2) in the above process (V) is not particularly limited, but examples include (1) a method of further reacting by adding a diamine when the ends of block (b1) and (b2) are acid anhydrides or derivatives thereof, (2) a method of further reacting by adding a tetracarboxylic acid dihydride or derivative thereof when the ends of block (b1) and (b2) are amine ends, and (3) a method of reacting block (b1) and block (b2) when block (b1) and (b2) have both an acid anhydride or derivative and an amine end.

[0125] The reaction between the diamine component and the tetracarboxylic acid component is typically carried out in an organic solvent. The organic solvent used at that time is not particularly limited as long as it dissolves the resulting polyimide precursor. Specific examples of organic solvents used in the reaction are given below, but are not limited to these examples. Examples include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or 1,3-dimethyl-2-imidazolidinone.

[0126] In addition, if the polyimide precursor has high solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or an organic solvent represented by the following formulas [D-1] to [D-3] may be used.

[0127] [Chemical Formula 27]

[0128]

[0129] Among the formula [D-1], D 1 represents an alkyl group having 1 to 3 carbon atoms, and in Formula [D-2], D 2 represents an alkyl group having 1 to 3 carbon atoms, and in formula [D-3], D 3 It represents an alkyl group having 1 to 4 carbon atoms.

[0130] These organic solvents may be used alone or in combination. Additionally, even if the solvent does not dissolve the polyimide precursor, it may be mixed with the said solvent and used within a range where the generated polyimide precursor does not precipitate.

[0131] The concentration of polyamic acid in the reaction system is preferably 1 to 30 mass%, and more preferably 5 to 20 mass%, in that it makes it difficult for polymer precipitation to occur and also makes it easy to obtain high molecular weight polymers.

[0132] The polyamic acid obtained as described above can be recovered by precipitating the polymer through injection into a solvent while stirring the reaction solution well. Additionally, by performing precipitation several times, washing with a solvent, and drying at room temperature or by heating, a purified polyamic acid powder can be obtained. The solvent is not particularly limited, but examples include water, methanol, ethanol, hexane, butyl cellosolve, acetone, toluene, etc.

[0133] <Preparation of Polyimide Precursors (Polyamic Acid Esters)>

[0134] The polyamic acid ester, which is a polyimide precursor used in the present invention, can be prepared, for example, by (1) an esterification reaction of a polyamic acid using an esterifying agent, (2) a reaction of a tetracarboxylic acid diester dichloride with a diamine, or (3) a polycondensation reaction of a tetracarboxylic acid diester with a diamine. The preparation method of (2) or (3) can be carried out in accordance with the preparation of the polyamic acid described above.

[0135] Among the three manufacturing methods above, the method of (1) or (2) is particularly preferred because it yields a high molecular weight polyamic acid ester.

[0136] The solution of polyamic acid ester obtained as described above can be injected into a solvent while stirring well to precipitate a polymer. After precipitation is performed several times and washing with a solvent, the product can be dried at room temperature or by heating to obtain a purified polyamic acid ester powder. The solvent is not particularly limited, but examples include water, methanol, ethanol, hexane, butyl cellosolve, acetone, toluene, etc.

[0137] <Manufacture of Polyimide>

[0138] The polyimide used in the present invention can be prepared by imidizing the polyimide precursor described above.

[0139] In the polyimide used in the present invention, the conversion rate of the amic acid group (also called the imidization rate) does not necessarily have to be 100% and can be arbitrarily adjusted according to the use or purpose.

[0140] For example, the imidization rate of the polyimide may be 20 to 100%, 50 to 99%, or 70 to 99% in order to increase the solubility of the polyimide varnish.

[0141] Imidation can be carried out by stirring the polyamic acid to be imidized in an organic solvent in the presence of a basic catalyst and an acid anhydride. As the organic solvent, the organic solvent used in the aforementioned polymerization reaction may be used. Examples of basic catalysts include pyridine, triethylamine, trimethylamine, tributylamine, and trioctylamine. Among these, pyridine is preferred because it possesses basicity suitable for carrying out the reaction. In addition, examples of acid anhydrides include acetic anhydride, trimellitic anhydride, and pyromellitic anhydride; among these, using acetic anhydride is preferred because it facilitates purification after the reaction is completed.

[0142] The temperature at which the above imidation reaction is carried out is -20 to 140 ℃, preferably 0 to 100 ℃, and the reaction time can be 0.5 to 100 hours, preferably 1 to 80 hours. The amount of basic catalyst is 0.5 to 30 mole times the amic acid, preferably 2 to 20 mole times, and the amount of acid anhydride is 1 to 50 mole times the amic acid, preferably 3 to 30 mole times. The imidation rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, and reaction time.

[0143] Since the added catalyst, etc. remains in the solution after the imidation reaction of the above-mentioned polyimide precursor, it is preferable to recover the obtained imidized polymer by means described below, redissolve it in an organic solvent, and use it as a component of the liquid crystal orientation agent of the present invention.

[0144] The polyimide solution obtained as described above can be injected into a solvent while stirring well to precipitate the polymer. After performing precipitation several times and washing with a solvent, the product can be dried at room temperature or by heating to obtain a purified polyimide powder.

[0145] The above-mentioned solvents are not particularly limited, but may include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, etc.

[0146] Polyimide Varnish

[0147] The polyimide varnish of the present invention contains the block copolymer described above. The content of the block copolymer in the polyimide varnish can be appropriately changed according to the setting of the thickness of the polyimide film to be formed. In terms of forming a uniform and defect-free film, 1 to 10 mass% of the total liquid crystal alignment agent is preferred, 2 to 9 mass% is more preferred, and 2 to 7 mass% is particularly preferred.

[0148] The polyimide varnish of the present invention preferably further contains at least one polymer (P) selected from the group consisting of a polyimide precursor having repeating units represented by the following formula (3) and a polyimide obtained by imidizing the polyimide precursor.

[0149] [Chemical Formula 28]

[0150]

[0151] (X3 represents a tetravalent organic group, preferably a tetravalent organic group derived from a tetracarboxylic acid dihydride. Y3 represents a divalent organic group derived from a diamine, preferably a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. R3 and Z3 have the same meaning as R1 and Z1 of Formula (1). The two existing R3 and Z3 each have the above definition independently.)

[0152] The polymer (P) preferably does not have a diphenylamine backbone. By additionally including the polymer (P), the properties of the polyimide varnish of the present invention (e.g., voltage retention rate and rubbing resistance of the liquid crystal alignment film obtained from the polyimide varnish) can be improved.

[0153] When the polyimide varnish of the present invention contains a polymer (P), the content ratio of the polymer (P) and at least one block copolymer selected from the group consisting of a polyimide precursor having the block (b1) and the block (b2), and a polyimide obtained by imidizing the polyimide precursor (hereinafter also referred to as block copolymer (b)), may be 10 / 90 to 90 / 10, 20 / 80 to 90 / 10, or 20 / 80 to 80 / 20 in mass ratio of [block copolymer (b)] / [polymer (P)].

[0154] In Equation (3), X3 is preferably, the following Equations (X3-1) to (X3-18), the above Equation (X 2a -1) ∼ (X 2a -2), (X 2a -5) represents at least one type selected from the group consisting of structures represented by -5. Preferred specific examples of the following formula (X3-13) include structures represented by the above formulas (X2-1) to (X2-4).

[0155] [Chemical Formula 29]

[0156]

[0157] (R 31 ~ R 34Each represents, independently, a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a benzene ring. j and k represent 0 or 1, and A1 and A2 represent, respectively, a single bond, -O-, -CO-, -COO-, a phenylene group, a sulfonyl group, or an amide group. The two A2s present each independently have the above definition.)

[0158] Preferred specific examples of the above (X3-17) and (X3-18) include the following formulas (X3-19) to (X3-34).

[0159] [Chemical Formula 30]

[0160]

[0161] In formula (3), Y3 preferably represents at least one type selected from the group consisting of the structure represented by Y1.

[0162] In formula (3), the two R3s are preferably each independently represented by a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. The two Z3s are preferably each independently represented by a hydrogen atom or an alkyl group having 1 carbon atom.

[0163] In equation (3), X3, Y3, R3, and Z3 may each be of one type or two or more types.

[0164] The above polyimide precursor is preferably composed of repeating units represented by the above formula (3).

[0165] The polymer (P) is more preferably such that the sum of the repeating unit (3) and the imidized structural unit of the repeating unit (3) is 10 to 100 mol% of the total repeating unit, and even more preferably 15 to 100 mol%.

[0166] Among these, X3 in the above formula (3) is (X3-1) to (X3-11), (X3-13) (more preferably (X2-1) to (X2-4)), or (X 2a -1) ∼ (X 2a -2) It is more preferable that the sum of the repeating unit (3) and the imidized structural unit of the repeating unit (3) is 10 to 100 mol% of the total repeating unit, and even more preferable that it is 15 to 100 mol%.

[0167] The polyimide varnish of the present invention has the effect of obtaining a high voltage retention rate or good orientation by additionally containing a polymer (P).

[0168] The polyimide varnish of the present invention can be prepared, for example, by dispersing or dissolving the block copolymer of the present invention, and optionally the polymer (P) and other components in an organic solvent.

[0169] Other ingredients include, for example, antioxidants (phenolic, phosphite-based, thioether-based, etc.), ultraviolet absorbers, hindered amine-based light stabilizers, nucleating agents, resin additives (fillers, talc, glass fibers, etc.), flame retardants, processability improvers, and active agents.

[0170] The above organic solvents include, for example, lactone solvents such as γ-valerolactone, γ-butyrolactone, etc.; lactam solvents such as γ-butyrolactam, amide solvents such as N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, etc.; 4-hydroxy-4-methyl-2-pentanone, 2,6-dimethyl-4-heptanone (diisobutyl ketone), methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol monomethyl ether, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, ethylene glycol-n-propyl ether, ethylene glycol-i-propyl ether, ethylene glycol-n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, Examples include diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monobutyl ether, propylene glycol diacetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, isoamyl propionate, isoamyl isobutyrate, diisopropyl ether, diisopentyl ether; carbonate solvents such as ethylene carbonate and propylene carbonate, 1-hexanol, cyclohexanol, 1,2-ethanediol, diisobutylcarbinol (2,6-dimethyl-4-heptanol), etc. These may be used alone or in a mixture of two or more.

[0171] Preferred solvent combinations include N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether, N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and diethylene glycol diethyl ether, N-ethyl-2-pyrrolidone and N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and diisobutyl ketone, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and dipropylene glycol monomethyl ether, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol monobutyl ether, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate, γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and diisobutyl ketone, γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether and diisobutyl ketone, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether and diisopropyl ether, Examples include N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether, and diisobutylcarbinol; N-methyl-2-pyrrolidone, γ-butyrolactone, and dipropylene glycol dimethyl ether; and N-methyl-2-pyrrolidone, propylene glycol monobutyl ether, and dipropylene glycol dimethyl ether. The type and content of such solvents are appropriately selected depending on the coating device, coating conditions, and coating environment of the liquid crystal alignment agent.

[0172] Liquid Crystal Alignment Agent

[0173] The liquid crystal alignment agent of the present invention is preferably prepared as a coating solution to be suitable for forming a liquid crystal alignment film. The liquid crystal alignment agent of the present invention may be prepared, for example, by dispersing or dissolving the polyimide varnish of the present invention and, if necessary, other components in an organic solvent.

[0174] Other components include, for example, crosslinkable compounds, functional silane compounds, surfactants, compounds having photopolymerizable groups, organic solvents, etc.

[0175] A crosslinkable compound can be used for the purpose of increasing the strength of a liquid crystal alignment film. Examples of such crosslinkable compounds include compounds having an isocyanate group or a cyclocarbonate group, or compounds having at least one group selected from the group consisting of lower alkoxyalkyl groups, as described in paragraphs

[0109] to

[0113] of International Publication WO2016 / 047771, as well as compounds having a block isocyanate group.

[0176] Block isocyanate compounds are available as commercial products, and, for example, colonate AP stable M, colonate 2503, 2515, 2507, 2513, 2555, mylonate MS-50 (all manufactured by Nippon Polyurethane Industry Co., Ltd.), takenate B-830, B-815N, B-820NSU, B-842N, B-846N, B-870N, B-874N, B-882N (all manufactured by Mitsui Chemical Co., Ltd.) can be preferably used.

[0177] Specific examples of desirable crosslinkable compounds include compounds represented by the following formulas (CL-1) to (CL-11).

[0178] [Chemical Formula 31]

[0179]

[0180] The above is an example of a crosslinkable compound and is not limited thereto. In addition, the crosslinkable compound used in the liquid crystal orientation agent of the present invention may be of one type or may be a combination of two or more types.

[0181] In the liquid crystal alignment agent of the present invention, the content of other crosslinkable compounds is 0.1 to 150 parts by mass, or 0.1 to 100 parts by mass, or 1 to 50 parts by mass, based on 100 parts by mass of all polymer components.

[0182] A functional silane compound can be used for the purpose of improving the adhesion between the liquid crystal alignment film and the underlying substrate. Specific examples include the silane compound described in paragraph

[0019] of International Publication No. 2014 / 119682. The content of the functional silane compound is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, per 100 parts by mass of all polymer components.

[0183] Surfactants may be used for the purpose of improving the uniformity of film thickness or surface smoothness of the liquid crystal alignment film. Examples of compounds include fluorine-based surfactants, silicone-based surfactants, and nonionic surfactants. Specific examples of these include the surfactant described in paragraph

[0117] of International Publication WO2016 / 047771. The amount of surfactant used is preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1 part by mass, per 100 parts by mass of all polymer components contained in the liquid crystal alignment agent.

[0184] Compounds having a photopolymerizable group include compounds having one or more polymerizable unsaturated groups, such as acrylate groups or methacrylate groups, within the molecule, such as compounds represented by the following formulas (M-1) to (M-7).

[0185] [Chemical Formula 32]

[0186]

[0187] In addition, the liquid crystal alignment agent of the present invention may include a nitrogen-containing heterocyclic amine compound represented by formulas [M1] to [M156], as described in paragraphs

[0194] to

[0200] of International Publication WO2011 / 132751 (published Oct. 27, 2011), more preferably 3-picolylamine and 4-picolylamine, as a compound that promotes charge transfer within the liquid crystal alignment film and promotes charge release from the device. This amine compound may be added directly to the liquid crystal alignment agent, but it is preferable to add it after preparing a solution with a concentration of 0.1 to 10 mass%, preferably 1 to 7 mass%. This solvent is not particularly limited as long as it dissolves the polyimide varnish.

[0188] In the case where the liquid crystal alignment agent of the present invention contains polyamic acid, polyamic acid ester, or polyamic acid-polyamic acid ester copolymer, an imidization promoter, etc., may be added for the purpose of efficiently promoting imidization by heating when firing the coating film.

[0189] The organic solvent contained in the liquid crystal alignment agent of the present invention is, for example, a lactone solvent such as γ-valerolactone, γ-butyrolactone, etc.; a lactam solvent such as γ-butyrolactam, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, etc.; an amide solvent such as N,N-dimethylformamide, N,N-dimethylacetamide, etc.; 4-hydroxy-4-methyl-2-pentanone, 2,6-dimethyl-4-heptanone, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol monomethyl ether, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, ethylene glycol-n-propyl ether, ethylene glycol-i-propyl ether, ethylene glycol-n-butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, Examples include diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monobutyl ether, propylene glycol diacetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, isoamyl propionate, isoamyl isobutyrate, diisopropyl ether, diisopentyl ether; carbonate solvents such as ethylene carbonate and propylene carbonate, 1-hexanol, cyclohexanol, 1,2-ethanediol, 2,6-dimethyl-4-heptanol, etc. These may be used alone or in a mixture of two or more.

[0190] Preferred solvent combinations include N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and ethylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether, N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and diethylene glycol diethyl ether, N-ethyl-2-pyrrolidone and N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and 2,6-dimethyl-4-heptanone, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and dipropylene glycol monomethyl ether, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol monobutyl ether, N-methyl-2-pyrrolidone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate, γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and 2,6-dimethyl-4-heptanone, γ-butyrolactone and 4-hydroxy-4-methyl-2-pentanone and propylene glycol diacetate, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanone, N-methyl-2-pyrrolidone and γ-butyrolactone and Examples include propylene glycol monobutyl ether and diisopropyl ether, N-methyl-2-pyrrolidone and γ-butyrolactone and propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanol, N-methyl-2-pyrrolidone and γ-butyrolactone and dipropylene glycol dimethyl ether, N-methyl-2-pyrrolidone and propylene glycol monobutyl ether and dipropylene glycol dimethyl ether. The type and content of such solvents are appropriately selected depending on the coating apparatus, coating conditions, and coating environment of the liquid crystal alignment agent.

[0191] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of components other than the organic solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected considering viscosity, volatility, etc., but is preferably in the range of 1 to 10 mass%.

[0192] The particularly preferred range of solid content concentration varies depending on the method used when applying the liquid crystal alignment agent to the substrate. For example, in the case of the spin coating method, a solid content concentration in the range of 1.5 to 4.5 mass% is particularly preferred. In the case of the printing method, it is particularly preferred to set the solid content concentration in the range of 3 to 9 mass%, thereby setting the solution viscosity in the range of 12 to 50 mPa·s. In the case of the inkjet method, it is particularly preferred to set the solid content concentration in the range of 1 to 5 mass%, thereby setting the solution viscosity in the range of 3 to 15 mPa·s.

[0193] <Liquid crystal alignment layer and liquid crystal display element>

[0194] The liquid crystal alignment layer of the present invention is obtained from the liquid crystal alignment agent. The liquid crystal alignment layer of the present invention can be used in a horizontal alignment type or a vertical alignment type liquid crystal alignment layer. The vertical alignment type liquid crystal alignment layer is a liquid crystal alignment layer preferred for a vertical alignment type liquid crystal display device, such as a VA method or a PSA mode. More preferably, the vertical alignment type liquid crystal alignment layer can be preferably used in a liquid crystal display device obtained by a method of manufacturing a liquid crystal display device in which a coating film is formed by applying it on a pair of substrates having conductive films, a liquid crystal cell is formed by arranging the coating films oppositely with a layer of liquid crystal molecules interposed therebetween, and light is irradiated onto the liquid crystal cell while a voltage is applied between the conductive films of the pair of substrates. More specifically, it is a liquid crystal display device for a PSA type liquid crystal display device or an SC-PVA mode liquid crystal display device described later. The liquid crystal display device of the present invention is equipped with the liquid crystal alignment layer. The liquid crystal display element of the present invention can be manufactured by a method including, for example, the following processes (1) to (3) or processes (1) to (4).

[0195] (1) Process of applying liquid crystal alignment agent onto a substrate

[0196] The liquid crystal alignment agent of the present invention is applied to one surface of a substrate having a patterned transparent conductive film formed thereon by an appropriate coating method, such as a roll coater method, a spin coat method, a printing method, or an inkjet method. Here, the substrate is not particularly limited as long as it is a highly transparent substrate, and in addition to glass substrates and silicon nitride substrates, plastic substrates such as acrylic substrates or polycarbonate substrates may also be used. Furthermore, in the case of a reflective liquid crystal display device, if only one side of the substrate is used, an opaque material such as a silicon wafer may be used, and in this case, a light-reflecting material such as aluminum may also be used for the electrode.

[0197] (2) Process of firing the coating

[0198] After applying the liquid crystal alignment agent, preheating (prebaking) is preferably performed first for purposes such as preventing the liquid of the applied alignment agent from dripping. The prebaking temperature is preferably 30 to 200°C, more preferably 40 to 150°C, and particularly preferably 40 to 100°C. The prebaking time is preferably 0.25 to 10 minutes, and more preferably 0.5 to 5 minutes. Then, it is preferable to perform a heating (postbaking) process.

[0199] The post-bake temperature is preferably 80 to 300°C, and more preferably 120 to 250°C. The post-bake time is preferably 5 to 200 minutes, and more preferably 10 to 100 minutes. The film thickness of the film formed in this way is preferably 5 to 300 nm, and more preferably 10 to 200 nm.

[0200] The film formed in the above process (1) can be used as is as a liquid crystal alignment film, but an alignment ability imparting treatment may be performed on the film. Examples of alignment ability imparting treatments include rubbing the film in a certain direction with a roll wound with a fabric made of fibers such as nylon, rayon, or cotton, and photoalignment treatment in which polarized or non-polarized radiation is irradiated onto the film.

[0201] In photo-alignment treatment, ultraviolet and visible light, including light with wavelengths of 150 to 800 nm, may be used as the radiation irradiated onto the coating film. When the radiation is polarized, it may be linearly polarized or partially polarized. Furthermore, when the radiation used is linearly polarized or partially polarized, irradiation may be performed from a direction perpendicular to the substrate surface, from a diagonal direction, or in combination thereof. When non-polarized radiation is irradiated, the direction of irradiation is diagonal.

[0202] (3) Process of forming a liquid crystal layer

[0203] (3-1) In the case of a VA type liquid crystal display element

[0204] Two substrates having liquid crystal alignment layers formed thereon are prepared as described above, and liquid crystal is placed between the two substrates arranged opposite each other. Specifically, the following two methods may be cited. The first method is a conventionally known method. First, two substrates are arranged opposite each other with a gap (cell gap) interposed so that each liquid crystal alignment layer faces the other. Next, the periphery of the two substrates is bonded using a sealant, and a liquid crystal composition is injected and filled into the cell gap partitioned by the substrate surface and the sealant to bring it into contact with the film surface, and then the injection hole is sealed.

[0205] In addition, the second method is a technique called the ODF (One Drop Fill) method. For example, a UV-curable sealant is applied to a predetermined location on one of two substrates on which a liquid crystal alignment film is formed, and a liquid crystal composition is additionally dropped onto several predetermined points on the surface of the liquid crystal alignment film. Then, the other substrate is laminated so that the liquid crystal alignment films face each other, and the liquid crystal composition is pressed and spread over the entire surface of the substrate to come into contact with the film surface. Subsequently, the sealant is cured by irradiating ultraviolet light onto the entire surface of the substrate. In either method, it is preferable to further remove the flow alignment during liquid crystal filling by heating the liquid crystal composition used to a temperature at which it takes on an isotropic phase, and then slowly cooling it to room temperature.

[0206] (3-2) When manufacturing a PSA type liquid crystal display element

[0207] Except for injecting or dropping a liquid crystal composition containing a polymerizable compound, the above (3-1) is the same. Examples of polymerizable compounds include polymerizable compounds represented by formulas (M-1) to (M-7).

[0208] (3-3) When a film is formed on a substrate using a liquid crystal orientation agent containing a compound having a polymerizable group

[0209] After performing the same as in (3-1) above, a method for manufacturing a liquid crystal display device may be adopted by undergoing a process of irradiating ultraviolet light as described later. According to this method, a liquid crystal display device with excellent response speed can be obtained with a small amount of light irradiation, similar to the case of manufacturing a PSA type liquid crystal display device. The compound having a polymerizable group may be a compound having one or more polymerizable unsaturated groups, such as acrylate groups or methacrylate groups represented by formulas (M-1) to (M-7), within the molecule, and the content thereof is preferably 0.1 to 30 parts by mass per 100 parts by mass of all polymer components, and more preferably 1 to 20 parts by mass. In addition, the polymerizable group may be present in the polymer used as a liquid crystal alignment agent, and such a polymer may be, for example, a polymer obtained by using a diamine component containing a diamine having the photopolymerizable group at the terminal end in the reaction.

[0210] (4) Process of irradiating with ultraviolet rays

[0211] Light is irradiated onto a liquid crystal cell while a voltage is applied between the conductive films of the pair of substrates obtained in (3-2) or (3-3) above. The voltage applied here can be, for example, 5 to 50 V direct current or alternating current. In addition, as the irradiating light, ultraviolet and visible light including light with a wavelength of, for example, 150 to 800 nm can be used, but ultraviolet light including light with a wavelength of 300 to 400 nm is preferred. As a light source for the irradiating light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc., can be used. The amount of light irradiated is preferably 1,000 to 200,000 J / m², and more preferably 1,000 to 100,000 J / m².

[0212] In addition, a liquid crystal display device can be obtained by laminating a polarizing plate to the outer surface of a liquid crystal cell. Examples of polarizing plates laminated to the outer surface of a liquid crystal cell include a polarizing plate in which a polarizing film called an "H film," which absorbs iodine while polyvinyl alcohol is stretched and oriented, is placed between cellulose acetate protective films, or a polarizing plate consisting of the H film itself.

[0213] The liquid crystal display element of the present invention can be effectively applied to various devices, and can be used in various display devices such as watches, portable games, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays.

[0214] Examples

[0215] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way by these examples.

[0216] <Synthesis of Liquid Crystal Alignment Agents>

[0217] The abbreviations used in the preparation of the liquid crystal orientation agent below are as follows.

[0218] (Tetracarboxylic acid dihydrogen)

[0219] BODA : Bicyclo[3,3,0]octane-2,4,6,8-tetracarboxylic acid dianhydride

[0220] CBDA: 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride

[0221] BDA: Meso-butane-1,2,3,4-tetracarboxylic acid dianhydride

[0222] (Diamine)

[0223] [Chemical Formula 33]

[0224]

[0225] (Additives)

[0226] [Chemical Formula 34]

[0227]

[0228] (menstruum)

[0229] NMP: N-methyl-2-pyrrolidone, BCS: Butylcellosolve

[0230] <Molecular Weight Measurement>

[0231] Measuring device: Room temperature gel permeation chromatography (GPC) manufactured by Senshu Kagaku (SSC-7200), Column: Column manufactured by Shodex (series of KD-803 and KD-805), Column temperature: 50 ℃, Eluent: N,N-dimethylformamide (as additives: lithium bromide monohydrate (LiBr·H2O) 30 mmol / L, crystalline anhydrous phosphoric acid (o-phosphoric acid) 30 mmol / L, tetrahydrofuran (THF) 10 ml / L), Flow rate: 1.0 mL / min,

[0232] Standard samples for calibration curve preparation: TSK standard polyethylene oxide manufactured by Tosoh Co. (molecular weights approx. 900,000, 150,000, 100,000, 30,000), and, polyethylene glycol manufactured by Polymer Laboratory Co. (molecular weights approx. 12,000, 4,000, 1,000).

[0233] <Measurement of Imide Conversion Rate>

[0234] 20 mg of polyimide powder was placed in an NMR sample tube (standard φ5 NMR sampling tube manufactured by Kusano Kagaku), 1.0 mL of deuterated dimethyl sulfoxide (DMSO-d6, 0.05 % TMS mixture) was added, and the solution was completely dissolved by applying ultrasound. The proton NMR of this solution at 500 MHz was measured using an NMR analyzer (JNW-ECA500) manufactured by Nihon Etsu Datum.

[0235] The chemical imidation rate was determined by determining a proton derived from a structure that does not change before and after imidation as a reference proton, and using the peak integration value of this proton and the peak integration value of the proton derived from the NH group of the amic acid appearing around 9.5 to 10.0 ppm, the following equation was used. In the equation, x is the peak integration value of the proton derived from the NH group of the amic acid, y is the peak integration value of the reference proton, and α is the ratio of the number of reference protons to one proton of the NH group of the amic acid in the case of polyamic acid (imidation rate 0%).

[0236] Imidization rate (%) = (1 - α·x / y) × 100

[0237] <Synthesized Example 1>

[0238] BODA (1.75 g, 7.0 mmol) and DA-5 (1.66 g, 8.4 mmol) were dissolved in NMP (13.7 g) and reacted at 60 °C for 3 hours, then DA-1 (1.12 g, 5.6 mmol) and NMP (4.5 g) were added and dissolved, then CBDA (1.31 g, 6.7 mmol) and NMP (5.3 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (1). The number average molecular weight Mn of this polyamic acid was 10,200, and the weight average molecular weight Mw was 38,400.

[0239] <Synthesized Example 2>

[0240] BODA (1.88 g, 7.5 mmol), DA-3 (0.65 g, 6.0 mmol) and DA-4 (1.18 g, 3.0 mmol) were dissolved in NMP (14.8 g) and reacted at 60 °C for 3 hours, then DA-1 (1.20 g, 6.0 mmol) and NMP (4.8 g) were added and dissolved, CBDA (1.41 g, 7.2 mmol) and NMP (5.6 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (2). The Mn of this polyamic acid was 11,200 and the Mw was 25,800.

[0241] <Synthesized Example 3>

[0242] BODA (0.75 g, 3.0 mmol) and DA-5 (2.08 g, 10.5 mmol) were dissolved in NMP (11.3 g) and reacted at 60 °C for 3 hours, then DA-2 (0.96 g, 4.5 mmol) and NMP (3.8 g) were added and dissolved, then CBDA (2.18 g, 11.1 mmol) and NMP (8.7 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (3). The Mn of this polyamic acid was 10,600 and the Mw was 28,700.

[0243] <Synthesized Example 4>

[0244] BODA (2.50 g, 10.0 mmol), DA-5 (0.99 g, 5.0 mmol), DA-6 (0.66 g, 2.0 mmol), DA-7 (1.42 g, 6.0 mmol), and DA-4 (2.76 g, 7.0 mmol) were dissolved in NMP (33.4 g) and reacted at 60 °C for 3 hours, after which CBDA (1.92 g, 9.8 mmol) and NMP (7.7 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution. NMP was added to this polyamic acid solution (25 g) to dilute it to 6.5 mass%, after which acetic anhydride (4.96 g) and pyridine (1.53 g) were added as imidization catalysts and reacted at 50 °C for 3 hours. This reaction solution was added to methanol (334 g), and the resulting precipitate was separated by filtration. The precipitate was washed with methanol and dried under reduced pressure at 60 °C to obtain polyimide powder. The imidization rate of this polyimide was 59%, Mn was 12,500, and Mw was 42,300. NMP (28.0 g) was added to the obtained polyimide powder (2.0 g) and dissolved by stirring at 70 °C for 15 hours. BCS (20.0 g) was added to this solution to obtain a polyimide solution (1).

[0245] <Synthesized Example 5>

[0246] BDA (2.58 g, 13.0 mmol), DA-8 (3.42 g, 14.0 mmol), and DA-9 (3.34 g, 6.0 mmol) were dissolved in NMP (52.9 g) and reacted at 50 °C for 2 hours, then CBDA (1.33 g, 6.8 mmol) and NMP (7.6 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution. NMP was added to this polyamic acid solution (25 g) to dilute it to 6.5 mass%, then acetic anhydride (3.59 g) and pyridine (1.11 g) were added as imidization catalysts and reacted at 40 °C for 2.5 hours. This reaction solution was added to methanol (250 g), and the resulting precipitate was separated by filtration. This precipitate was washed with methanol and dried under reduced pressure at 60°C to obtain polyimide powder. The imidization rate of this polyimide was 65%, Mn was 11,200, and Mw was 38,100. NMP (28.0 g) was added to the obtained polyimide powder (2.0 g) and dissolved by stirring at 70°C for 15 hours. BCS (20.0 g) was added to this solution to obtain a polyimide solution (2).

[0247] <Comparative Synthesis Example 1>

[0248] BODA (1.75 g, 7.0 mmol), DA-5 (1.66 g, 8.4 mmol), and DA-1 (1.12 g, 5.6 mmol) were dissolved in NMP (18.1 g) and reacted at 60 °C for 3 hours, then CBDA (1.31 g, 6.7 mmol) and NMP (5.2 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (4). The Mn of this polyamic acid was 11,100 and the Mw was 31,900.

[0249] <Comparative Synthesis Example 2>

[0250] BODA (1.88 g, 7.5 mmol), DA-3 (0.65 g, 6.0 mmol), DA-4 (1.18 g, 3.0 mmol) and DA-1 (1.20 g, 6.0 mmol) were dissolved in NMP (19.6 g) and reacted at 60 °C for 3 hours, then CBDA (1.41 g, 7.2 mmol) and NMP (5.5 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (5). The Mn of this polyamic acid was 10,000 and the Mw was 20,200.

[0251] <Comparative Synthesis Example 3>

[0252] BODA (0.75 g, 3.0 mmol), DA-5 (2.08 g, 10.5 mmol), and DA-2 (0.96 g, 4.5 mmol) were dissolved in NMP (15.2 g) and reacted at 60 °C for 3 hours, then CBDA (2.18 g, 11.1 mmol) and NMP (8.7 g) were added and reacted at 40 °C for 4 hours to obtain a polyamic acid solution (6). The Mn of this polyamic acid was 9,400 and the Mw was 34,200.

[0253] The specifications of each polymer obtained in the above synthesis examples and comparative synthesis examples are as shown in Table 1 below.

[0254]

[0255] <Preparation of Liquid Crystal Alignment Agents>

[0256] In the examples and comparative examples, examples of liquid crystal alignment agents are described. Using the liquid crystal alignment agents obtained in the examples and comparative examples, the manufacture of liquid crystal display devices and various evaluations were carried out.

[0257] [Example 1]

[0258] A liquid crystal orientation agent (A-1) was obtained by adding NMP (16.0 g) and BCS (16.0 g) to the polyamic acid solution (1) (8.0 g) obtained in Synthesis Example 1 and stirring at room temperature for 2 hours.

[0259] [Examples 2, 3, Comparative Examples 1–3]

[0260] Liquid crystal alignment agents (A-2), (A-3), (B-1) to (B-3) of Examples 2 and 3 and Comparative Examples 1 to 3 were obtained by performing the same procedure as in Example 1, except that polyamic acid solutions (2) to (6) were used instead of polyamic acid solution (1).

[0261] [Example 4]

[0262] A liquid crystal aligner (C-1) was obtained by mixing the polyimide solution (1) (3.0 g) obtained in Synthesis Example 4, the liquid crystal aligner (A-1) (7.0 g) obtained in Example 1, and AD-1 (0.04 g).

[0263] [Examples 5, 6, Comparative Examples 4–6]

[0264] Liquid crystal alignment agents (C-2), (C-3), (D-1) to (D-3) of Examples 5 and 6 and Comparative Examples 4 to 6 were obtained by performing the same procedure as Example 4, except that liquid crystal alignment agents (A-2), (A-3), (B-1) to (B-3) were used instead of liquid crystal alignment agent (A-1), respectively.

[0265] [Example 7]

[0266] A liquid crystal aligner (C-4) was obtained by mixing the polyimide solution (2) (3.0 g) obtained in Synthesis Example 5 and the liquid crystal aligner (A-1) (7.0 g) obtained in Example 1.

[0267] [Example 8, Comparative Examples 7, 8]

[0268] Liquid crystal alignment agents (C-5), (D-4), and (D-5) of Example 8 and Comparative Examples 7 and 8 were obtained by performing the same procedure as in Example 7, except that liquid crystal alignment agents (A-3), (B-1), and (B-3) were used instead of liquid crystal alignment agent (A-1), respectively.

[0269] It was confirmed that the liquid crystal alignment agents obtained as described above (A-1) to (A-3), (B-1) to (B-3), (C-1) to (C-5), and (D-1) to (D-5) were uniform solutions without any abnormalities such as turbidity or precipitation. Using the obtained liquid crystal alignment agents, the transmittance was evaluated, the liquid crystal cell was manufactured, the voltage retention rate was evaluated, and the residual DC voltage was evaluated.

[0270] [Evaluation of Transmittance]

[0271] Liquid crystal alignment agents (A-1) to (A-3), (C-1) to (C-5), (B-1) to (B-3), and (D-1) to (D-5) obtained in the examples and comparative examples were spin-coated onto a quartz substrate and dried on a hot plate at 70°C for 90 seconds. Afterward, the substrate was fired in an IR (infrared) oven at 230°C for 20 minutes to form a film with a thickness of 100 nm, thereby obtaining a substrate with a liquid crystal alignment film formed thereon. With this substrate with the liquid crystal alignment film formed thereon placed inside, another quartz substrate was used, and a refractive solution (contact solution manufactured by Shimadzu Devices) was placed between them to prevent light interference. For the evaluation of transmittance, a UV-3600 (manufactured by Shimadzu Corporation) was used as a measuring device, and measurements were taken at a temperature of 25°C and a scan wavelength of 380 to 800 nm. At that time, two uncoated quartz substrates with a refractive liquid in between were used as a reference. The evaluation was based on the transmittance at a wavelength of 580 nm, and the value is shown in Table 2 below. An example of the relationship between wavelength and transmittance is shown in Figure 1.

[0272] [Manufacture of Liquid Crystal Display Devices for Voltage Retention Rate and Residual DC Characteristics Evaluation]

[0273] A liquid crystal cell was manufactured in the following order using the liquid crystal alignment agents (A-1) to (A-3), (C-1) to (C-3), (B-1) to (B-3), and (D-1) to (D-3) obtained in the examples and comparative examples. The liquid crystal alignment agent was spin-coated onto a glass substrate with an ITO electrode attached, dried on a hot plate at 70°C for 90 seconds, and then fired in an IR oven at 230°C for 20 minutes to form a liquid crystal alignment film with a thickness of 100 nm. Two substrates having this liquid crystal alignment film formed thereon were prepared, a bead spacer with a diameter of 4 μm (manufactured by Nikki Catalytic Chemical Co., Ltd., Jinsagu, SW-D1) was applied on the liquid crystal alignment film of one of the substrates, and a thermosetting sealant (manufactured by Mitsui Chemical Co., Ltd., XN-1500T) was printed. Next, with the side of the other substrate where the liquid crystal alignment film is formed facing inward, it was bonded to the preceding substrate, and then the sealant was cured to produce an empty cell. Liquid crystal MLC-3023 (manufactured by Merck) was injected into this empty cell by a reduced pressure injection method to produce a liquid crystal cell. Next, with a DC voltage of 15 V applied to this liquid crystal cell, UV light passing through a cut filter of 325 nm or less was irradiated at 10 J / cm² from the outside of the liquid crystal cell. In addition, the UV irradiance was measured using a UV-MO3A manufactured by ORC. Afterwards, in order to inactivate unreacted polymerizable compounds remaining in the liquid crystal cell, UV (UV lamp: FLR40SUV32 / A-1) was irradiated for 30 minutes using a UV-FL irradiation device manufactured by Toshiba Litec while no voltage was applied.

[0274] [Manufacturing of Liquid Crystal Display Devices for Evaluating Afterimage Characteristics]

[0275] Liquid crystal cells were manufactured in the order shown below using the liquid crystal alignment agents (A-2), (C-1) to (C-3), (B-2), (D-1) to (D-3) obtained in the examples and comparative examples. A liquid crystal alignment agent was spin-coated onto the ITO surface of an ITO electrode substrate (length: 35 mm, width: 30 mm, thickness: 0.7 mm) having an ITO electrode pattern formed with a pixel size of 200 μm × 600 μm and a line / space of 3 μm each, and a glass substrate (length: 35 mm, width: 30 mm, thickness: 0.7 mm) having an ITO electrode attached with a photospacer patterned with a height of 3.2 μm, and then dried on a hot plate at 70°C for 90 seconds, followed by firing in an IR oven at 230°C for 20 minutes to form a liquid crystal alignment film with a film thickness of 100 nm. In addition, the ITO electrode substrate on which the ITO electrode pattern is formed is divided into four sections in a cross-checker (checkered pattern) shape and is configured to be driven separately for each of the four areas.

[0276] Next, a seal (XN-1500T manufactured by Mitsui Chemicals) was printed. Subsequently, with the side of the other substrate where the liquid crystal alignment film was formed facing inward, it was attached to the preceding substrate, and the seal was cured to manufacture a blank cell. Liquid crystal MLC-3023 (manufactured by Merck) was injected into this blank cell by a reduced pressure injection method to manufacture a liquid crystal cell. With a DC voltage of 15 V applied to this liquid crystal cell, UV light passing through a cut filter of 325 nm or less was irradiated at 10 J / cm² from the outside of the liquid crystal cell. In addition, the UV irradiance was measured using a UV-MO3A manufactured by ORC. Afterwards, in order to inactivate unreacted polymerizable compounds remaining in the liquid crystal cell, UV (UV lamp: FLR40SUV32 / A-1) was irradiated for 30 minutes using a UV-FL irradiation device manufactured by Toshiba Litec without applying voltage.

[0277] [Evaluation of Voltage Maintenance Rate]

[0278] The voltage retention rate was measured using a liquid crystal cell for evaluating the voltage retention rate after UV irradiation. A voltage of 1 V was applied for 60 μs in a hot air circulation oven at 60 ℃, and the voltage was measured after 16.67 msec to calculate the voltage retention rate, which indicates how long the voltage could be maintained. A VHR-1 manufactured by Toyo Technica was used to measure the voltage retention rate. The values ​​are shown in Table 2 below.

[0279] [Evaluation of Residual DC Voltage]

[0280] For the liquid crystal cell for voltage retention rate evaluation manufactured above, a square wave of 30 Hz and 7.8 Vpp superimposed with 2 V DC was applied at 25 ℃ for 100 hours, and the voltage remaining in the liquid crystal cell (residual DC voltage) after 1 hour of cutting off the DC voltage was determined by the flicker elimination method. The values ​​are shown in Table 2 below.

[0281] [Afterimage Characteristics]

[0282] Using the liquid crystal cell for evaluating afterimage characteristics manufactured above, an AC voltage of 60 Hz and 20 Vp-p was applied to two diagonal areas among the four pixel areas, and driven for 168 hours at a temperature of 25 ℃. Afterwards, all four pixel areas were driven with an AC voltage of 5 Vp-p, and the difference in pixel brightness was observed visually. A state in which the difference in brightness was almost imperceptible was considered good, and the evaluation results are shown in Table 2.

[0283] [Loving Resistance]

[0284] The liquid crystal alignment agents (C-4), (C-5), (B-1), (B-3), (D-4), and (D-5) obtained in the examples and comparative examples were spin-coated onto the ITO surface of a glass substrate with ITO electrodes attached to the entire surface, and temporarily dried on a hot plate at 70°C for 90 seconds. Afterwards, the substrate was fired in an IR oven at 230°C for 20 minutes to form a film with a thickness of 100 nm, thereby obtaining a substrate with a liquid crystal alignment film. This liquid crystal alignment film was rubbed with a rayon cloth (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.6 mm). The substrate was observed under a microscope, and the results were evaluated as "good" if no streaks caused by rubbing were visible on the film surface, and "poor" if streaks were visible. The results are shown in Table 2.

[0285]

[0286] As shown in Table 2 and Figure 1, in the evaluation results of transmittance using liquid crystal alignment agents (A-1) to (A-3) and (C-1) to (C-5) obtained in Examples 1 to 8, it can be seen that a liquid crystal alignment film with a high transmittance is obtained when compared with the evaluation results of transmittance using liquid crystal alignment agents (B-1) to (B-3) and (D-1) to (D-5) obtained in the corresponding Comparative Examples 1 to 8. Furthermore, a 1% difference in transmittance is a significant difference in the art. On the other hand, in the evaluation of voltage retention rate, residual DC voltage, afterimage characteristics, and rubbing resistance, it can be seen that a liquid crystal alignment film having the same degree of characteristics is obtained.

[0287] In addition, the liquid crystal display device using the liquid crystal alignment agents (C-1) to (C-3) exhibited high voltage retention characteristics compared to the liquid crystal display device using the liquid crystal alignment agents (A-1) to (A-3). That is, by mixing a polyimide solution (1) that does not have a diphenylamine backbone, a liquid crystal alignment film having high transmittance is obtained, and a liquid crystal display device with high voltage retention is obtained.

[0288] In addition, the liquid crystal display device using the above liquid crystal alignment agents (C-4) and (C-5) exhibited good rubbing resistance. That is, by mixing a polyimide solution (2) that does not have a diphenylamine backbone, a liquid crystal alignment film having high transmittance is obtained, and a liquid crystal display device exhibiting good rubbing resistance is obtained.

[0289] In addition, the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2020-044505 filed on March 13, 2020 are incorporated herein by reference and accepted as disclosure of the specification of the present invention.

Claims

Claim 1 A polyimide varnish containing at least one block copolymer selected from the group consisting of a polyimide precursor having a block (b1) having a repeating unit represented by the following formula (1) and a block (b2) having a repeating unit represented by the following formula (2), and a polyimide obtained by imidizing the polyimide precursor. (X1 represents at least one type selected from the group consisting of structures represented by the following formulas (X1-1) ~ (X1-4), (X1-7), (X1-9) and (X1-11). X2 represents a tetravalent organic group derived from an acyclic aliphatic tetracarboxylic acid dihydride or a tetravalent organic group represented by the following formula (X2). Y1 represents a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. Y2 represents a divalent organic group having a diphenylamine backbone. Two R1s and R2s each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and two Z1s and Z2s each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms that may have substituents, an alkenyl group having 2 to 10 carbon atoms that may have substituents, an alkynyl group having 2 to 10 carbon atoms that may have substituents, a tert-butoxycarbonyl group, or a 9-fluorenylmethoxycarbonyl group. (R 21 ~ R 24 Each represents, independently, a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a phenyl group. Claim 2 A polyimide varnish according to claim 1, wherein in formula (1), Y1 represents at least one type selected from the group consisting of a divalent organic group having 3 to 50 carbon atoms having a structure represented by the following formulas (S1) to (S3), and a divalent organic group having 3 to 50 carbon atoms not having a structure represented by the formulas (S1) to (S3) (provided that the divalent organic group having 3 to 50 carbon atoms having a structure represented by the formulas (S1) to (S3) and the divalent organic group having 3 to 50 carbon atoms not having a structure represented by the formulas (S1) to (S3) do not have a diphenylamine backbone). (X 1 and X 2 is, each independently, single bond, -(CH2) a - (a is an integer from 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -COO-, -OCO- or -((CH2) a1 -A1) m1 - represents. Among these, a1 is independently an integer from 1 to 15, A1 is independently an oxygen atom or -COO-, and m1 is from 1 to 2. G 1 and G 2 represents, respectively, a divalent cyclic group selected from a divalent aromatic group having 6 to 12 carbon atoms and a divalent alicyclic group having 3 to 8 carbon atoms. Any hydrogen atom on the cyclic group may be substituted. m and n are each independently integers from 0 to 3, and m + n is 1 to 4. R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms, and R 1 Any hydrogen atom forming may be substituted with a fluorine atom. If m, n, and m1 are 2 or more, there are multiple Xs. 1 , X 2 , G 1 , G 2 , a1, m1, and A1 each independently have the above definition.) (X 3 It represents a single bond, -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CH2O-, -COO-, or -OCO-. R 2 represents an alkyl group having 1 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms, and R 2 Any hydrogen atom forming it may be replaced with a fluorine atom.) (X 4 represents -CONH-, -NHCO-, -O-, -CH2O-, -COO-, or -OCO-. R 3 It represents a structure having a steroid backbone. Claim 3 A polyimide varnish according to claim 2, wherein in formula (1), at least one of Y1 represents a divalent organic group having 3 to 50 carbon atoms having a structure represented by formulas (S1) to (S3). Claim 4 A polyimide varnish according to claim 2 or 3, wherein in formula (1), at least one of Y1 represents a divalent organic group having 3 to 50 carbon atoms that does not have a structure represented by formulas (S1) to (S3). Claim 5 A polyimide varnish according to claim 2, wherein a divalent organic group having 3 to 50 carbon atoms that does not have a structure represented by formulas (S1) to (S3) comprises a divalent organic group having a nitrogen-containing heterocyclic ring within the molecule, a divalent organic group having a radical initiation function, a divalent organic group having a carboxyl group, a group having "-N(D)-" (where D represents a tert-butoxycarbonyl group), a group having photo-oriented properties, a divalent organic group having an oxygen-containing heterocyclic ring, or a divalent organic group derived from an aromatic diamine that does not have a side chain group having 3 or more carbon atoms. Claim 6 A polyimide varnish according to any one of claims 1 to 3, wherein in formula (2), X2 represents at least one type selected from the group consisting of structures represented by the following formulas (X2-1) to (X2-4). Claim 7 A polyimide varnish according to any one of claims 1 to 3, wherein in formula (2), Y2 represents a structure represented by the following formula (d2). (A1 represents a single bond, -NR- (R represents a hydrogen atom or a monovalent organic group), -O-, -C(=O)-, -C(=O)NR- (R represents a hydrogen atom or a monovalent organic group), -C(=O)O-, or a divalent organic group. R1 and R2 each independently represent a hydrogen atom or a monovalent organic group. If n is 2, multiple A1 and R2 exist, each independently having the above definition.) Claim 8 A polyimide varnish according to any one of claims 1 to 3, wherein the ratio of the total number of moles of repeating units represented by formula (1) to the total number of moles of repeating units represented by formula (2) per molecule of block copolymer is 1:9 to 9:

1. Claim 9 A polyimide varnish according to any one of claims 1 to 3, further comprising at least one polymer (P) selected from the group consisting of a polyimide precursor having repeating units represented by the following formula (3) and a polyimide obtained by imidizing the polyimide precursor. (X3 represents a tetravalent organic group. Y3 represents a divalent organic group having 3 to 50 carbon atoms that does not have a diphenylamine backbone. R3 and Z3 have the same meaning as R1 and Z1 in Formula (1). The two existing R3 and Z3 each have the above definition independently.) Claim 10 In claim 9, the polymer (P) is a polyimide varnish that does not have a diphenylamine backbone. Claim 11 A method for manufacturing a polyimide varnish according to any one of claims 1 to 3, comprising: a process (I) of reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (1-T) with a diamine component comprising a diamine represented by the following formula (1-D) to obtain a block (b1); and a process (II) of adding to the block (b1) a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (2-T) and a diamine component comprising a diamine represented by the following formula (2-D) and reacting them to obtain a polyimide precursor having block (b1) and block (b2). (X1, X2, Y1, and Y2 are the same as those defined in Equations (1) and (2).) Claim 12 A method for manufacturing a polyimide varnish according to claim 11, wherein the reaction temperature in process (II) is lower than the reaction temperature in process (I). Claim 13 A method for manufacturing a polyimide varnish according to any one of claims 1 to 3, comprising: a process (III) of reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (1-T) with a diamine component comprising a diamine represented by the following formula (1-D) to obtain a block (b1); a process (IV) of reacting a tetracarboxylic acid component comprising a tetracarboxylic acid dihydride or a derivative thereof represented by the following formula (2-T) with a diamine component comprising a diamine represented by the following formula (2-D) to obtain a block (b2); and a process (V) of coupling the block (b1) obtained in the process (III) with the block (b2) obtained in the process (IV) to obtain a polyimide precursor having the block (b1) and the block (b2). (X1, X2, Y1, and Y2 are the same as those defined in Equations (1) and (2).) Claim 14 A method for manufacturing a polyimide varnish according to claim 13, wherein the reaction temperature in process (IV) is lower than the reaction temperature in process (III). Claim 15 A liquid crystal orientation agent obtained from a polyimide varnish described in any one of claims 1 to 3. Claim 16 A liquid crystal alignment film formed using the liquid crystal alignment agent described in claim 15. Claim 17 A liquid crystal display element having a liquid crystal alignment layer as described in claim 16. Claim 18 A method for manufacturing a liquid crystal display device, wherein a liquid crystal alignment agent described in claim 15 is applied onto a pair of substrates having conductive films to form a coating film, a liquid crystal cell is formed by arranging the coating films oppositely with a layer of liquid crystal molecules interposed therebetween, and light is irradiated onto the liquid crystal cell while a voltage is applied between the conductive films of the pair of substrates. Claim 19 delete

Citation Information

Patent Citations

  • Liquid crystal aligning agent, liquid crystal alignment membrane, liquid crystal display element, and method for manufacturing liquid crystal display element

    KR1020140108570A

  • Liquid crystal aligning agent for in-plate switching, liquid crystal alignment film and liquid crystal display element using same

    KR1020160067132A

  • Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element

    KR1020170131548A